IMPLEMENTASI PROFIL PELAJAR PANCASILA DALAM PEMBELAJARAN PENDIDIKAN PANCASILA KELAS IV UPT SD NEGERI 16 KELARA KABUPATEN JENEPONTO - Junaedah, Dea Ananda; Bhakti Prima Findiga Hermuttaqien; Muhammad Nur Abdullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the importance of strengthening students’ character through the values of Pancasila, amidst various moral issues occurring in school environments. The Pancasila Student Profile, as the core foundation of the Merdeka Curriculum, aims to develop Indonesian students who are faithful, pious, globally diverse, collaborative, independent, critical thinkers, and creative individuals. However, its implementation in elementary schools faces several challenges such as limited facilities, time constraints, and diverse student backgrounds that affect the learning process. This study aims to examine the implementation of the Pancasila Student Profile in the Pancasila Education learning process for fourth-grade students at UPT SD Negeri 16 Kelara, Jeneponto Regency. This research uses a descriptive qualitative approach with data collection techniques including interviews, observations, and documentation. The findings show that (1) lesson planning has been conducted by formulating learning objectives, materials, activities, and assessments aligned with the dimensions of the Pancasila Student Profile. The planning also includes differentiation strategies to accommodate varying student abilities. (2) Learning implementation involves methods such as lectures, group discussions, presentations, and project-based learning. Students are actively engaged in activities that cultivate cooperation, appreciation of diversity, critical thinking, and creativity, and the values of Pancasila are practiced directly in classroom interactions. (3) Assessment and evaluation are carried out continuously through diagnostic, formative, and summative assessments that cover cognitive, affective, and psychomotor domains using instruments such as written tests, observations, student journals, project assessments, and self-reflections. sThe study concludes that the implementation of the Pancasila Student Profile has been generally effective and contributes positively to student character development. However, further improvement is needed in terms of facility provision and teacher competency enhancement to ensure sustainable and optimal program implementation.